Islam Jawa Sebagai Sumber Ide Penciptaan Karya Grafis - Iqbal Misbahuddin M (Kusa Lawa, 2021)
Java as one of the largest landmasses in Indonesia has many unsolved mysteries until now because it is considered as mystical and forbidden to touch for the inexperienced. For a long time, Java made a history that many people can still feel, from the history of power, mysticism, culture to religious affairs. In the beginning, Java itself already had a belief in the strongest entity called God and already had its own thoughts on how God exists and is felt. Some people recognize that belief as animism and dynamism, which believes that certain spirits or objects have a power that is considered their God, others consider Java to have a more complex religion or belief which is often called Kejawen, Kapitaian, Sundanese Wiwitan, and so on. If drawn straight with the beliefs recognized today it is believed by some to have the same as the teachings of Islam. Why can it be called similar to Islamic teachings, because there are some beliefs that believe that there is only one God who must be worshiped for them in a predetermined manner. From this restlessness, the writer wants to dissect these problems into graphic art works.